1899
DOI: 10.1002/cber.18990320256
|View full text |Cite
|
Sign up to set email alerts
|

Zur Kenntniss des Diazotirungsprocesses

Abstract: Auffallender Weise liegen auch nur annahernd quantitative Best imrnungen iibei. den Diazotirungsprocess') und die Diazotirungsgeschwindigkeit der Anilinbasen noch nicht Tor, obgleich dieser Vorgang zu den allerwichtigsten grhort, und ein genaueres Studium seiner Geschwindigkeit und ihrer Beeinflussung durch aussere Factoren wohl von allgemeineni Interesse ist. Das Vorhandensein dieser Liicke liegt zum Theil wohl darin, dass schon nach qualitativer Schiitzung die Diazotirung ungemeiii rasch verlauft, zurn Theil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1900
1900
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Nitrosamines are known to be generated via the reaction of nitrite and amines under acidic conditions (reaction ). Many researchers have reported that reaction is a second-order reaction. , The following are reaction pathways of the second-order reaction: In recent year, Hughes and others proposed a third-order reaction. Reaction pathways of the third-order reaction are explained below. However, the pathways of the third-order reaction are not widely accepted.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrosamines are known to be generated via the reaction of nitrite and amines under acidic conditions (reaction ). Many researchers have reported that reaction is a second-order reaction. , The following are reaction pathways of the second-order reaction: In recent year, Hughes and others proposed a third-order reaction. Reaction pathways of the third-order reaction are explained below. However, the pathways of the third-order reaction are not widely accepted.…”
Section: Introductionmentioning
confidence: 99%